ANALISA MARKETING KONTEN UNTUK MEREK FASHION LOKAL INDONESIA PADA INSTAGRAM - Erwita, Monica Adjeng; Handayani, Yuliasti Ika (Jurnal Manajemen, 2022)
The purpose of this paper is to analyze digital marketing strategy on Instagram among local brand fashion in Indonesia by assessing the content marketing and consumer engagement to build competitive advantages. This research is using content analysis method. A content analysis of 196 social media posts was conducted from the Instagram accounts of 2 local brand fashions in Indonesia during two months between December 2020 and January 2021. The data collected from each social media post generated by those brands were coded and analyzed in terms of their marketing content and consumer engagement. This research found that brand, product information, photo, and consumer appreciation were frequently appearing and effective for informative marketing content. Meanwhile, conversations about brand and product which are consist of quality, emotion, relations, and services were the frequently appearing topics in the comment column and its effective for consumer engagement. This paper has limitation, it focused only on Instagram. From practitioners’ perspectives, the findings can help local brands to enhance social media marketing effectiveness with content marketing and consumer engagement.